Sistem Informasi Pengadaan Barang ATK Di PT. Mekar Cipta Indah Menggunakan Php Dan Mysql - Agung Wahana; Asep Ririh Riswaya (STMIK Mardira Indonesia, Bandung, 2013)
The author makes writing material derived from research in PT. Mekar Cipta Indah. In research that has been done can be observed how the systems work on the GA (General Affairs) that handles stationery supplies, was in demand for office stationery, office stationery stock records, and reports are still done manually. In relation to the business world, computers as a means of data, is an appropriate means to process any business transactions. Manually because the documentation is not possible anymore, because the more volume of transactions taking place and is very influential on office stationery supplies. Then the application program has become a vital requirement for any organization or company to streamline its business operations. With the computerization, it is in the data processing will be more effective, safer, reduce errors, and archives can be arranged neatly. In order for a system that can work well done, the authors sought to design a system in the office supplies stationery. Currently the author uses PHP program language that outlines program focuses on the stock, and to design this system, the authors make the design process of data entry that contains the stationery. Keywords: program design; program office stationery supplies